The influence of the guide’s personal brand on the formation of trust in author’s excursions in a competitive environment - Motorina, Anastasiia (Актуальні питання економічних наук, 2025)
With the growing diversification of tourism services and increased competition in the market, author-led tours are becoming increasingly relevant due to their uniqueness, emotional intensity, and the guide’s leading role as a key figure in the tourist experience. The relevance of this research is further reinforced by the rising importance of digital self-presentation, social media activity, and online reviews, which create a new reality of interaction between guides and potential clients even before the tour begins. The purpose of the article is to analyze the relationship between the personal brand of a guide and the formation of consumer trust in the segment of the author’s excursions, as well as to identify effective branding practices that enhance competitiveness. Methods: analysis of scientific literature – to study the current state of the research issue; generalization and systematization – to clearly and consistently present the research results. Results. It is demonstrated that a well-formed and strategically supported personal brand has a significant impact on the level of trust, particularly in contexts of information overload and high market saturation. Elements such as authenticity, emotional openness, professional expertise, and consistent storytelling through various communication channels create a multidimensional image of a tour guide that tourists perceive as reliable and attractive. The presence of a personal brand reduces uncertainty in decision-making and increases customer loyalty, particularly when the guide’s online and offline representations are aligned. The analysis of practical cases shows that guides who specialize in thematic content, actively engage with their audiences on social platforms, and respond to feedback are more successful in building long-term relationships and generating repeat bookings. The conclusions confirm that a personal brand serves not only as a marketing asset but also as a trust-building mechanism, forming both the emotional and rational basis for choosing excursions. In the long term, personal branding becomes a key factor in the sustainable development of a guide’s professional career and the overall competitiveness of an author’s excursions in the modern mobile tourism environment.